Unique allergen-specific human IgE monoclonal antibodies derived from patients with allergic disease - Smith, Bryan R. E.; Reid Black, Kristina; Bermingham, Max; Agah, Sayeh; Glesner, Jill; Versteeg, Serge A.; van Ree, Ronald; Pena-Amelunxen, Glorismer; Aglas, Lorenz; Smith, Scott A.; Pomés, Anna; Chapman, Martin D. (Frontiers in Allergy, 2023)
Abstract Introduction Allergic reactions are mediated by human IgE antibodies that bind to and cross link allergen molecules. The sites on allergens that are recognized by IgE antibodies have been difficult to investigate because of the paucity of IgE antibodies in human serum. Here, we report the production of unique human IgE monoclonal antibodies to major inhaled allergens and food allergens that can be produced at scale in perpetuity. Methods The IgE antibodies were derived from peripheral blood mononuclear cells of symptomatic allergic patients, mostly children aged 3-18, using hybridoma fusion technology. Total IgE and allergen specific IgE was measured by ImmunoCAP. Specificity was confirmed by ELISA and by immunoblotting. Allergenic potency measurements were determined by ImmunoCAP inhibition. Biologic activity was determined in vitro by comparing β-hexosaminidase release from a humanized rat basophilic cell line. Results Human IgE monoclonal antibodies (n=33) were derived from 17 allergic patients with symptoms of allergic rhinitis, asthma, atopic dermatitis, food allergy, eosinophilic esophagitis or red meat allergy. The antibodies were specific for 5 inhaled allergens, 9 food allergens and alpha-gal, and had very high levels of IgE (53,450-1,702,500 kU/L) with ratios of specific IgE to total IgE ranging from <0.01-1.39. Sigmoidal allergen binding curves were obtained by ELISA, with low limits of detection (<1 kU/L). Allergen specificity was confirmed by immunoblotting. Pairs of IgE monoclonal antibodies to Ara h 6 were identified that cross-linked following allergen stimulation and induced release of significant levels of β-hexosaminidase (35-80%) from a humanized rat basophilic cell line. Conclusions Human IgE monoclonal antibodies are unique antibody molecules with potential applications in allergy diagnosis, allergen standardization and the identification of allergenic epitopes for development of allergy therapeutics. The IgE antibody probes will enable the unequivocal localization and validation of allergenic epitopes.